In vitro Evaluation of Anti-inflammatory Protein-Denaturation Activity of Cashew (Anacardium occidentale Linn) Stem Bark Using a UV–Vis Spectrophotometer - Jangga; Sri Wahyuningsih; Abdul Wahid Suleman; Sulaiman (Jurnal Penelitian Pendidikan IPA, 2025)
Inflammation is a protective response of the body caused by tissue damage due to abnormal physical conditions, harmful chemical compounds, or microbiological agents. The protein denaturation method for anti-inflammatory testing aims to determine whether the ethyl acetate and ethanol–water fractions of cashew (Anacardium occidentale Linn) stem bark exhibit anti-inflammatory activity using the protein denaturation method, and to determine the IC₅₀ values of both fractions. The anti-inflammatory activities of the ethyl acetate and ethanol–water fractions, along with the positive control, were tested using a UV–Vis spectrophotometer at concentrations of 100 ppm, 200 ppm, 400 ppm, 800 ppm, and 1600 ppm. The results showed that the ethyl acetate fraction of cashew stem bark (Anacardium occidentale L.) had an IC₅₀ value of 531.74 µg/mL, the ethanol–water fraction had an IC₅₀ value of 101.31 µg/mL, and the positive control had an IC₅₀ value of –70.85 µg/mL. These findings indicate that the ethanol–water fraction exhibited moderate anti-inflammatory activity, while the ethyl acetate fraction showed weak activity.